Mediation Effects Of Capital Structure And Profitability On The Influence Of Sales Growth On Firm Value In Consumer Goods Companies - Cindy Natalia; Eka Desy Purnama; Lambok DR Tampubolon (Fakultas Bisnis, 2021)
Firm value is important for a company thus, many companies compete with other companies to get better Firm value. A company that has a good Firm value is considered having a better performance so that it becomes an attraction that can increase Firm value. Firm value of a company can be recognized from stock price in the stock market which is called Indonesia Stock Exchange. Investors are seen as a determinant of Firm value. The higher Firm value of a company describes that the company’s performance is in a good condition. When the investors catch a good signal from the company, it will encourage them to buy the shares. This research is a quantitative study which aims to find out the influence of Sales Growth to the Firm value of a company that is mediated by Capital Structure and Firm value. This study uses Consumer Goods Companies that are listed in Indonesia Stock Exchange and the financial reports used range from 2015 to 2019. This study used nonrandom sampling which is Purposive Sampling to obtain 26 out of 60 companies to be tested with five sub-sectors, namely: Cosmetics and Household, Food and Beverages, House ware, Pharmaceuticals, and Tobacco Manufacturers. Multiple linear regression analysis technique using SPSS system version 25. Sales Growth Variable (X), Capital Structure (Z1) and Profitability (Z2) have an effect on Firm value (Y) with determinant value R2 = 40.9%, Sales Growth Variable (X) affects Capital Structure (Z1) with determinant value R2 = 39.5% and Sales Growth (X) to Profitability (Z2) with determinant value R2 = 4.5%. In the t test, it can be concluded that Sales Growth has no effect on Firm value. Capital Structure and Profitability have an effect on Firm value. Sales Growth has a significant positive effect on Capital Structure and a significant negative impact on Profitability. The mediating variable, which is Capital Structure, is able to act as mediator between Sales Growth and Firm value while profitability is unable to act as mediator between Sales Growth and Firm Value